Amnesti: Hak Prerogatif Presiden dalam Perspektif Fiqh Siyasah - Sinta Kartika Putri; Mutiara Fahmi Razali; Azmil Umur (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2022)
This article examines the granting of amnesty to perpetrators of political crimes by the President of the Republic of Indonesia. This authority is regulated in the Basic Law of the Republic of Indonesia, 1945, Article 14 paragraph (2), and Emergency Law Number 11, 1954, Article 1 on Amnesty and Abolition. Both of these rules do not specifically describe the limitations or types of criminal acts that amnesty may be granted to. The amnesty granted by the President to Baiq Nuril, a victim of sexual harassment involved in cases of infringement of the Information and Electronic Transactions Act, was carried out on the basis of humanity and justice. This policy has influenced the historical changes in amnesty law aimed at non-political cases. The study aims to examine the authority of the President of Indonesia in granting amnesty, reviewed from a fiqh siyasah perspective. Data is obtained through library studies and analyzed using a normative or doctrinal approach. The results of the study show that the granting of amnesty by the president is a prerogative of the president, as stipulated in the Basic Law of the Republic of Indonesia 1945. But in fiqh siyasah, the essence of amnesty is forgiveness. Forgiveness is the prerogative of the head of state, aimed at creating greater crimes, and does not violate the provisions of the law that have been established. The President's policy of granting amnesty in non-political cases is in accordance with the provisions of the fiqh siyasah, because the concept of amnesty in the law and the notion of forgiveness in the fiqh siyasah are equally based on the interests of the state and the crime of the community. Historical facts show that the Prophet Muhammad and the caliphs after him gave forgiveness to rebels, war criminals, and non-political criminals.